regulatory genome: gene regulatory networks in development and evolution - Davidson, Eric H (Elsevier/Academic Press, 2006)
Gene regulatory networks are the most complex, extensive control systems found in nature. The interaction between biology and evolution has been the subject of great interest in recent years. The author, Eric Davidson, has been instrumental in elucidating this relationship. He is a world renowned scientist and a major contributor to the field of developmental biology. The Regulatory Genome beautifully explains the control of animal development in terms of structure/function relations of inherited regulatory DNA sequence, and the emergent properties of the gene regulatory networks composed of these sequences. New insights into the mechanisms of body plan evolution are derived from considerations of the consequences of change in developmental gene regulatory networks. Examples of crucial evidence underscore each major concept. The clear writing style explains regulatory causality without requiring a sophisticated background in descriptive developmental biology. This unique text supersedes anything currently available in the market. * The only book in the market that is solely devoted to the genomic regulatory code for animal development * Written at a conceptual level, including many novel synthetic concepts that ultimately simplify understanding * Presents a comprehensive treatment of molecular control elements that determine the function of genes * Provides a comparative treatment of development, based on principles rather than description of developmental processes * Considers the evolutionary processes in terms of the structural properties of gene regulatory networks * Includes 42 full-color descriptive figures and diagrams